2004
DOI: 10.1002/poc.739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non‐ionic and mixed non‐ionic–cationic micelles on the rate of aqueous cleavages of phenyl benzoate and phenyl salicylate in alkaline medium

Abstract: Pseudo‐first‐order rate constants (kobs) for the hydrolysis of phenyl salicylate (PSH) and phenyl benzoate (PB) in the alkaline medium show a monotonic decrease with the increase in [C16E20]T (total concentration of Brij 58) at constant [CH3CN] and [NaOH]. This micellar effect is explained in terms of the pseudophase model of micelles. These results show a characteristic difference between the effects of [C16E20]T and previously published effects of [C12E23]T (total concentration of Brij 35) on the rates of aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
1
19
1
Order By: Relevance
“…It has been observed that an increase in the total concentration of cetyltrimethylammonium bromide ([CTABr] T ) from 0.0 to 0.03 M has no effect on the apparent pK a of the conjugate acid of 4 in the presence of 0.02 M C 12 E 23 [15], which is considered to be unusual in view of our understanding (through pseudophase ion exchange model of micelle) of the occurrence of ion exchange of HO À /Br À at CTABr micellar surface [16][17][18]. The observed kinetic data (k obs vs. [C m E n ] T ), reported in earlier studies [9][10][11][12][13][14][15], failed to obey PM model at greater than the typical values of R t (=[C m E n ] T /[HO À ] T ). The plausible reason(s) for such observations remained unknown.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…It has been observed that an increase in the total concentration of cetyltrimethylammonium bromide ([CTABr] T ) from 0.0 to 0.03 M has no effect on the apparent pK a of the conjugate acid of 4 in the presence of 0.02 M C 12 E 23 [15], which is considered to be unusual in view of our understanding (through pseudophase ion exchange model of micelle) of the occurrence of ion exchange of HO À /Br À at CTABr micellar surface [16][17][18]. The observed kinetic data (k obs vs. [C m E n ] T ), reported in earlier studies [9][10][11][12][13][14][15], failed to obey PM model at greater than the typical values of R t (=[C m E n ] T /[HO À ] T ). The plausible reason(s) for such observations remained unknown.…”
Section: Introductionmentioning
confidence: 57%
“…But the values of R t were 88 and $5 at respective 1.0 and 0.76 mM NaOH for C 16 E 10 as well as 140 at 1.0 mM NaOH for C 16 E 20 [12]. In all these studies [9][10][11][12], the observed data, obtained at R < R t , have been explained in terms of PM model. The unusual near irreversible trapping of moderately hydrophobic reactants by C m E n micelles at R P R t cannot be attributed to the usual shielding effect of micelles [12].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Recently, the effects of non-ionic-cationic micelles on the aqueous cleavages of phenyl benzoate and phenyl salicylate in alkaline solution have been studied and the micellar effect was explained in terms of a pseudophase model of micelles coupled with changes in micellar environment of the system [8].…”
Section: Introductionmentioning
confidence: 99%